Perceived parenting styles and primary attachment styles of single and children living with both parents - Mehr-un-Nisa Idrees; Syeda Mehreen Zahra; Fatima Naeem (Journal of the Pakistan Medical Association, 2021)
Objective: The study investigates the association between perceived primary parenting styles and attachment styles between single parent children and children living with both parents. Methods: A correlational research study was carried out on a sample of 200 children, 100single parent children (Boys=50; Girls=50) taken from single parent families living in child protection and welfare bureau and 100 children living with both parents (Boys=50; Girls=50) enrolled in different grades taken from a private school of Lahore, through purposive sampling strategy. The study was carried out at Lahore Garrison University from September 2017 to march 2017.After obtaining permission from authorities, children were given Parental Authority Questionnaireand the Urdu version of Inventory of Parental and Peer attachment. Results:The results showed that there was a significant negative correlation between permissive parenting styles with mother’scommunication (*p<.05); authoritarian parenting style has negative correlation with parental communication, and trust(***p<.001). Authoritative parenting has significant positive relationship with trust (***p<.001), and communication with parents (***p<.001), negative relationship between authoritative parenting with feeling alienated from parents (*p<.01). The resultsof t-test also revealed that single parent children perceive their parents as authoritarian (***p<.001) and had more alienated attachment with parents (***p<.001), whereas children living with both parents had more trust (***p<.001) and had better communication with their parents (***p<.001). Conclusion: Current research is insightful in understanding the role of parents and different parenting styles in building up strong parent child attachment. Continuous...